Do Board of Commissioners Characteristic and International Environmental Certification Affect Carbon Disclosure? Evidence from Indonesia - Yumna Rifdatul Ummah; Doddy Setiawan (Jurnal Dinamika Akuntansi dan Bisnis, 2021)
The purpose of this study is to examine the influence of the characteristics of the board of commissioners and international environmental certification on the disclosure of carbon emissions. Populations of this study are financial and non-financial companies listed on the Indonesia Stock Exchange (IDX) between 2015 and 2019. Panel data regression is employed to analysis data that collected from annual reports and sustainability reports of the sample companies. The results show that size of board of commissioners and the proportion of independent commissioners have a negative effect on the disclosure of carbon emissions. Gender diversity of the board of commissioners has a positive effect on the disclosure of carbon emissions, while nationality diversity and international environmental certification have no effect on the disclosure of carbon emissions